Village lots, La Brea, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Photo of village lots on the banks of a body of water at La Brea, Trinidad.
Colour: Black and White ; Style: Landscape ; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Villages; Dwellings